2020
DOI: 10.1002/nag.3166
|View full text |Cite
|
Sign up to set email alerts
|

Permeability stability calculation model of foam‐conditioned soil based on the permeability constant

Abstract: The low permeability of discharged muck must last for at least tens of minutes to avoid water spewing during earth pressure balance (EPB) shield tunneling; however, foam, which is usually added to soil to reduce its permeability, has its own unique time‐varying characteristics. Thus, it is important to predict the stable time of permeability of foam‐conditioned soil for EPB shield tunneling. Based on theories of the effective permeation channel of pure foam and fluid mechanics, a constant is proposed to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Figure 7 shows that the auxiliary air pressure mode slightly helps to prevent spewing when the auxiliary air pressure is taken as the lower design limit, but the critical permeability coefficients of the different full chamber rates gradually converge when the water pressure h1 at the bottom of the cutter face is greater than 16 m. And when h1 is greater than 28 m, the critical permeability coefficient will be less than 10 -4 cm/s and this value will be smaller as the auxiliary air pressure increases, at which point the permeability coefficients given in the recommendations of Wang SY et al [11], Budach C and Thewes M [12] will be at risk of spewing. In addition, the reduction of the permeability coefficient to 1×10 -5 cm/s obviously meets the impermeability requirements of the shield tunnels.…”
Section: Fig 7 Critical Permeability Coefficients At Different Water ...mentioning
confidence: 96%
See 3 more Smart Citations
“…Figure 7 shows that the auxiliary air pressure mode slightly helps to prevent spewing when the auxiliary air pressure is taken as the lower design limit, but the critical permeability coefficients of the different full chamber rates gradually converge when the water pressure h1 at the bottom of the cutter face is greater than 16 m. And when h1 is greater than 28 m, the critical permeability coefficient will be less than 10 -4 cm/s and this value will be smaller as the auxiliary air pressure increases, at which point the permeability coefficients given in the recommendations of Wang SY et al [11], Budach C and Thewes M [12] will be at risk of spewing. In addition, the reduction of the permeability coefficient to 1×10 -5 cm/s obviously meets the impermeability requirements of the shield tunnels.…”
Section: Fig 7 Critical Permeability Coefficients At Different Water ...mentioning
confidence: 96%
“…In this paper, the parameters h1 and h2 can be determined based on the engineering conditions and existing studies, and the unknowns An, Bm, Cl, Dj, and hAB can be determined by Eqs. ( 9), ( 13), (22), and (26). After trial calculation, the analytical solution converges and the calculation time is within 2s when the series term N≥40, and N=40 is taken for all the analyses in the following.…”
Section: Analytical Solution For the Seepage In The Screw Conveyormentioning
confidence: 99%
See 2 more Smart Citations
“…Borio and Peila (2010) carried out constant head permeability tests under different water pressures to study the permeability of foam-conditioned sand and found that the permeability coefficient of foam-conditioned sand decreased with an increase in the foam injection ratio (FIR, which is defined as the ratio of the volume of foam to that of a soil specimen in the natural loose state) but increased with an increase in the foam expansion ratio (FER, which is defined as the ratio of the volume of foam to that of foam solution) and water pressure. However, because foam is a metastable multiphase system with an uneven bubble size (Pitois et al 2009;Rouyer et al 2014), the permeability of foam-conditioned sand has a certain temporal variability; that is, the permeability coefficient (k) is maintained at a low level in the initial period; however, as the foam bubbles continue to dissipate and are flushed out over time, k increases rapidly, and after a fast growth period, it finally stabilizes (Budach 2012;Hu et al 2020;Wang et al 2021). Hu et al (2020) studied the effect of hydraulic gradients on the permeability characteristics of foam-conditioned sand.…”
Section: Introductionmentioning
confidence: 99%